Strain Rate Analysis on the Çankiri-Bingöl Segment of the North Anatolian Fault in Turkey (2015)
The North Anatolian Fault Zone (NAFZ) is one of the most important fault zones of Turkey and the world. It has produced several high magnitude earthquakes that have resulted in massive loss of lives and resources. National and international research on the North Anatolian Fault zone that Turkey resides on have been realized to better understand and predict the earthquakes produced by it. This study focuses on the Çankırı – Bingöl segment of the NAFZ. The aim of this study is to calculate the strain and latent earthquake potential of the studied area. For this purpose, geodetic data coming from several individual projects have been merged. Strain values have been calculated from the combined data and regions on the fault zone, and strain accumulations have been presented graphically. After calculation, Çankırı, Amasya and Kelkit regions were analyzed. The compressional and extensional deformation has been shown in north and south part of Çankırı basin, respectively. Eastern adjacent area of the Çankırı basin, Amasya region, has the primary branch of the NAF and its subbranches. In the Amasya region, the deformation is mostly on the main branch and the earthquake potential has risen to it. The Kelkit Valley has complex structures and inhomogeneous dispersion. Southeastern and Northwestern part of the Kelkit Valley has varied deformation in micro scale. Consequently, the study results indicate that strain accumulation is concentrated on areas such as the Çankırı basin, Amasya region, and various areas in the Kelkit Valley from west to east. Análisis de la Velocidad de Deformación en el Segmento Çankırı-Bingöl de la Falla de Anatolia del Norte, Turquía. ResumenLa Zona de la Falla de Anatolia del Norte (NAFZ, del inglés North Anatolian Fault Zone) es una de las zonas de fallas más importantes de Turquía y del mundo. Esta falla ha generado varios terremotos de gran magnitud que han resultado en pérdidas humanas y de recursos. La investigación nacional e internacional de la Zona de la Falla de Anatolia del Norte, que atraviesa Turquía, se ha realizado con el fin de un mejor entendimiento y predicción de los terremotos que allí se originan. Este análisis se enfoca en el segmento Çankırı-Bingöl de la NAFZ. El objetivo es calcular la tensión y el potencial de terremoto del área de estudio. Con este propósito se recopiló la información geodésica de varios proyectos individuales. Los valores de tensión se calcularon de la información combinada de las regiones que componen la zona de falla y se presentan gráficamente las acumulaciones de tensión. Tras el cálculo de estos valores se analizaron las regiones Çankırı, Amasya y Kelkit. La deformación de compresión y la de extensión aparecen al norte y al sur de la cuenca Çankırı, respectivamente. El área ubicada al Este de la cuenca Çankırı, la región de Amasya, posee la rama principal de la NAFZ y sus subdivisiones. En la región de Amasya la deformación se presenta en la rama principal de la NAFZ, donde se eleva el potencial de movimientos sísmicos. El valle de Kelkit tiene estructuras complejas y dispersión no homogénea. El sudeste y el noroeste del valle Kelkit muestran una deformación variada a microescala. Los resultados de este estudio indican que la acumulación de tensión se concentra en la cuenca Çankırı, la región Amasya y varias áreas del valle Kelkit desde el oeste hacia el este.